TECHNOLOGY OF LABORATORY INVESTIGATIONS OF TEMPORARY CHANGES PYROELECTRIC PARAMETERS OF ROCKS - Vyzhva, S.; Onyshchuk, V.; Reva, M.; Onyshchuk, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article discusses the features of methods of petroelectrical investigations in rocks used at the laboratory of theoretical and applied geophysics of ESI ‘'Institute of Geology",Taras Shevchenko National University of Kyiv. The authors have also presented the results of experimental investigations of the electrical resistance fluctuations of extracted rock samples in time as well as the induced polarization potentials (IP) of rock samples saturated by solution. As a result of pilot laboratory works improved non-standard method of laboratory tests has applied to determine electrical properties of rocks. The technology of laboratory researches of fluctuations of petroelectrical parameters at direct current in time of rock samples extracted and saturated by model of reservoir water is developed with using digital megohmmeter C.A. 6547 and multimeter UT-70B. To asses the possibility in using the recorded non-stationary processes at determination ofthe physical and chemical properties of rocks novel methods of processing and analysis of results of laboratory digital records of temporal fluctuations of the electrical resistance of dry rock samples and induced polarization potentials of rock samples saturated by solution is developed. The developed method is based on usage of two parameters of polarization – polarizability and polarization rate. Polarization rate is the derivative of polarizability. It characterizes the rate of changes of the polarizability in time (unit of measurement – percentage / a second). The polarization rate is a petroelectrical parameter rarely used in laboratory petrophysical researches before. According to the results of laboratory measurements, the polarization rate has more stable correlation with physical and chemical properties of rocks than their polarizability. Thus, the polarization rate in combination with polarizability could be used to build complex petroelectrical models.
Keywords: rock; petrophysical researches; physical properties; ectrical resistance; polarizability; polarization rate; petroelectrical parameter